Faktor-faktor yang Mempengaruhi Manajemen Perawatan Luka di Apotek Komunitas Indonesia: Sebuah Studi Lintas Sektoral - Lusy Noviani; Dwi Arymbhi Sanjaya; Ni Kadek Refi Mariska; Pretty Falena Atmanda Kambira (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Wound care remains a major public health problem, particularly in low- and middle-income countries (LMICs) such as Indonesia. Pharmacists practicing in community-based primary care settings are often the first point of contact for patients with minor wounds, yet evidence describing their wound care practices in routine care remains limited. This study aimed to describe wound care practices among pharmacists in community-based primary care settings in Indonesia and to examine factors associated with wound care product selection, product availability, and patient education. A cross-sectional online survey was conducted among pharmacists practicing in community-based primary care settings in Indonesia. The study used a non-probability convenience sampling approach, with recruitment through online pharmacist communication networks and professional social media platforms. A structured questionnaire was used to collect data on respondent characteristics, factors influencing wound care product selection, product availability, and patient education practices. Descriptive statistics were used to summarize the data, and associations between categorical variables were analyzed using the Fisher’s Exact test. A total of 303 pharmacists were included in the analysis. The median age of respondents was 33 years (range: 23–74 years). Most respondents practiced in community pharmacies (83.5%). Across all experience groups, wound type and severity were the most commonly considered factors in wound care product selection. Other clinical considerations and product availability varied by years of practice and practice setting. Most respondents reported routinely providing patient education during wound care consultations. These findings describe variation in wound care practices among pharmacists in community-based primary care settings in Indonesia.